FACIES ANALYSIS AND STATIC RESERVOIR MODELING IN MATINDAS FIELD, A, B, AND C INTERVALS, BEKASAP FORMATION, CENTRAL SUMATRA BASIN - YOLANDA MATINDAS ( NIM : 12010106), YUDITH
Administratively, Matindas Field is located in Riau Province which is encompassing an area of 26,25 km2. Matindash Field, is a downthrown part of thrust fault and also an assymetrical anticline with northwest-southeast trend. Reservoirs in Matindas Field are parts of Bekasap Formation. The study is focusing on three reservoir intervalS within the Bekasap Formation which are Reservoir C, Reservoir B, and Reservoir A. The main purposes of this study are to know the geological setting of research area, determine reservoir characterization such as depositional faseis, reservoir properties and the distribution, and also hydrocarbon prospect in C, B, and A Reservoirs interval of Bekasap Formation. The data used in this research consists of 3D cube and 2D seismic line (depth domain), core, and well log data. Several methods have been performed in order to achive those main purposes which are electrofacies, sequence stratigraphy, formation evaluation, and static reservoir modelling. The facies analysis with electrofacies approach method which was validated to core data in Sumur-73 shows that all reservoir intervals were deposited in estuarine. Reservoir C in tidal-fluvial channel, Reservoir B in tidal bar, and Reservoir A in tidal channel and tidal bar. Based on reservoir properties analysis, the best reservoir quality is fluvial-tidal channel in Reservoir C and followed by tidal bar in Reservoir B, and tidal channel in Reservoir A. The correlation of stratigraphy sequence showed that the reservoirs were in 1st and 2nd sequence intervals. Based on geostatistical analysis and hydrocarbon volumetric calculation, reservoir modelling concludes that the amount of hydrocarbon reserve in Reservoir C is 22.48x106 STB, Reservoir B is 9.57x106 STB, and Reservoir A is 4.7x106 STB. Total estimation of hydrocarbon volumetric at Matindas Field is 36.75x106 STB. Those informations can be used as reference for oil field development plan in Bekasap Formation at Matindas Field.